1991
DOI: 10.1093/ajcn/54.1.215s
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium and blood pressure: modifying factors in specific populations

Abstract: Epidemiologic findings continue to add to the body of evidence supporting a relationship between calcium intake and blood pressure. These findings also indicate that there is a threshold of the potential protective effect of adequate calcium intake, below which the risk of hypertension increases at a greater rate. The set point of this threshold, estimated at 700-800 mg/d, may be modified by a variety of factors including dietary patterns and components, lifestyle, and genetics. This may explain, at least in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…study, which indicated that baseline calcium was important for a dairy‐mediated blood pressure response. There is strong evidence that the magnitude of the beneficial effect of dairy foods and calcium on blood pressure may be threshold dependent . For instance, additional calcium in habitually low consumers may lower blood pressure; however, blood pressure may not improve in those with normal calcium status.…”
Section: Dairy Consumption and Blood Pressurementioning
confidence: 99%
“…study, which indicated that baseline calcium was important for a dairy‐mediated blood pressure response. There is strong evidence that the magnitude of the beneficial effect of dairy foods and calcium on blood pressure may be threshold dependent . For instance, additional calcium in habitually low consumers may lower blood pressure; however, blood pressure may not improve in those with normal calcium status.…”
Section: Dairy Consumption and Blood Pressurementioning
confidence: 99%
“…A possible threshold for the effect of dairy products and dietary calcium on blood pressure has been suggested at a calcium intake of 700-800 mg/d (28). About half of the participants in the milk group had a calcium intake at baseline that exceeded this limit.…”
Section: Effects Related To Habitual Calcium Intakementioning
confidence: 99%
“…[65][66][67] Furthermore, epidemiological studies confirm an inverse correlation between Ca 2ϩ intake and blood pressure in specific human populations. 68,69 Several potential mechanisms that may explain the effect of calcium on blood pressure have been proposed, including changes in the secretion of calcium-regulating hormones, such as PTH and parathyroid hypertensive factor. However, there has been little or no consideration to the hypothesis that changes in Ca 2ϩ o concentration may modify the blood pressure through the CaR.…”
Section: Potential Roles Of the Car In Regulating Blood Pressurementioning
confidence: 99%